Challenges to Gene Editing Approaches in the Retina - Bonillo, Mario; Pfromm, Julia; Fischer, M. Dominik (Klinische Monatsblätter für Augenheilkunde, 2022)
Retinal gene therapy has recently been at the cutting edge of clinical development in the diverse field of genetic therapies. The retina is an attractive target for genetic therapies such as gene editing due to the distinctive anatomical and immunological features of the eye, known as immune privilege, so that inherited retinal diseases (IRDs) have been studied in several clinical studies. Thus, rapid strides are being made toward developing targeted treatments for IRDs. Gene editing in the retina faces a group of heterogenous challenges, including editing efficiencies, off-target effects, the anatomy of the target organ, immune responses, inactivation, and identifying optimal application methods. As clustered regularly interspaced palindromic repeats (CRISPR)/CRISPR-associated nuclease (Cas) based technologies are at the forefront of current gene editing advances, their specific editing efficiency challenges and potential off-target effects were assessed. The immune privilege of the eye reduces the likelihood of systemic immune responses following retinal gene therapy, but possible immune responses must not be discounted. Immune responses to gene editing in the retina may be humoral or cell mediated, with immunologically active cells, including microglia, implicated in facilitating possible immune responses to gene editing. Immunogenicity of gene therapeutics may also lead to the inactivation of edited cells, reducing potential therapeutic benefits. This review outlines the broad spectrum of potential challenges currently facing retinal gene editing, with the goal of facilitating further advances in the safety and efficacy of gene editing therapies.
Keywords: retina; genetics; molecular biology